Assessment the Effect of Dexamethasone on Urinary Cytokines and Renal Scar in Children with Acute Pyelonephritis (Iranian Journal of Kidney Diseases, 2019)
Introduction. One of the most serious complications of acute febrilepyelonephritis in children is the development of renal scar. Thisstudy aimed to investigate the effect of dexamethasone on urinarycytokine levels and renal scar in children with acute pyelonephritis.Methods. In a double-blind randomized clinical trial, 60 childrenaged 3 months to 12 years with acute febrile pyelonephritis enrolled.The experimental group was treated with a combination of antibioticand dexamethasone, and the control group underwent treatmentwith antibiotic and placebo. The urinary levels of interleukin -6(UIL-6) and -8 (UIL-8) were measured before treatment as baselineand were repeated four days later.Results. 52 cases (23 patients with mean age of 34.19 ± 30.82 monthsin the dexamethasone group, and 29 patients with mean age of50.55 ± 44.41 months in the control group) completed the study. Inthe control group, the UIL-6 and UIL-8 level became significantlylower after four days treatment (P < .05). In the dexamethasonegroup, there was a statistically significant difference between bothUIL-6 and UIL-8 levels before and after treatment (P < .05). Inpatients who had scar on DMSA scan, the mean UIL-8 and UIL-6levels were significantly high before and after treatment.Conclusion. Results of this study showed that dexamethasone plusantibiotic have no clear superiority to antibiotic therapy alone indecreasing inflammatory cytokines and scar formation. We foundout that patients with scar had sustained high levels of biomarkersbefore and after treatment.